The Virtual Screening of Compounds from the ZINC Database against PARP-1 in Triple-Negative Breast Cancer - Priyankha, Sridhar; Polk, Shahrazad; Thilagavathi, Ramasamy; Prakash, Muthuramalingam; Kathiravan, M. K.; Lakshmana Prabhu, Sakthivel; Brunozi de Oliveira, Isabela [UNESP]; Selvam, Chelliah (Wiley, 2024)
Triple-negative breast cancer (TNBC) is the most aggressive kind of breast cancer that has disseminated worldwide, decimating millions of people. Especially, since it is capable of forming complex mutations, the design and development of effective drugs are much needed. Clinically, though talazoparib is an FDA-approved drug for PARP against advanced breast cancer, it has several adverse side effects such as anaemia, alopecia, neutropenia and thrombocytopenia. Herein, to understand the molecular interactions and mode of binding, 4.59 million lead-like compounds from the ZINC database were virtually screened against poly(ADP-ribose) polymerase-1 (PARP-1) protein using molecular docking. ADMET analysis were also performed for these compounds. Molecular dynamics (MD) simulations were conducted for a period of 100 ns for the best five compounds to validate the stability of the complexes. Root-mean-square deviation (RMSD), root-mean-square fluctuation (RMSF), and the radius of gyration (Rg) were analyzed and the number of hydrogen bonding interactions was identified to determine the structure and stability of these protein-ligand complexes. Further, binding free energy calculations were performed using the molecular mechanics-Poisson-Boltzmann surface area (MM/PBSA) approach to identify the effective anticancer agents. Z02, Z03, and Z04 have the highest binding affinity of −19.6, −18.1, and −18.1 kcal/mol, respectively, with PARP-1. They also have been found to strongly enhance the stability of the target. All things considered; we determine that compound Z04 is the most promising hit for TNBC.
Keywords: Molecular dynamics simulations; Molecular mechanics-Poisson-Boltzmann surface area; PARP inhibitors; Poly(ADP-ribose) polymerase; Triple-negative breast cancer